Cannabis use is associated with low plasma endocannabinoid Anandamide in individuals with psychosis. (May 2023) - Bassir Nia, Anahita; Gibson, Claire L; Spriggs, Sharron A; Jankowski, Samantha E; DeFrancisco, Daniel; Swift, Amy; Perkel, Charles; Galynker, Igor; Honrao, Chandrashekhar; Makriyannis, Alexandros; Hurd, Yasmin L
Background: Cannabis use suppresses the endocannabinoid system in healthy individuals. However, the association between cannabis use with the endocannabinoid system is understudied in individuals with psychosis despite the high rate of cannabis use in these individuals. Methods: We enrolled 83 individuals who were admitted to an inpatient psychiatric unit with psychotic presentations, and measured their plasma levels of main endocannabinoids, Anandamide (AEA) and 2-Acylglycerol (2-AG), and endocannabinoid related compounds, Palmitoylethanolamine, and N-oleoylethanolamine. Cannabis use was assessed with urine toxicology and frequency of cannabis use was assessed using self-reported questionnaires. The Positive and Negative Syndrome Scale was used to assess the severity of psychotic symptoms. Results: Overall, we had 38 individuals in cannabis positive group (CN+) and 45 individuals in cannabis negative group (CN−). Compared to CN−, CN+ group had lower plasma levels of AEA, which remained significant after controlling for age, gender, race/ethnicity, and use of other drugs. Conclusion: Cannabis use is associated with low plasma AEA levels in individuals with psychosis, which is in the same line with reported suppressive effects of cannabis on the endocannabinoid system in healthy individuals. Further studies are needed to investigate the clinical significance of this finding.